KEMAMPUAN BERPIKIR REFLEKTIF MATEMATIS SISWA DENGAN MENGGUNAKAN MODEL CONNECTED MATHEMATICS PROJECT (CMP) SMP NEGERI 7 LANGSA - N, F, Nuzul; Saiman (Jurnal Dimensi Matematika, 2023)
This research aims to analyze the existence of students' mathematical reflective thinking abilities after using the Connected Mathematics Project (CMP) learning model at SMP Negeri 7 Langsa. And another aim is to show that students' mathematical reflective thinking abilities in the experimental class after experiencing learning using the connected mathematics project (CMP) model are better than those in the control class after experiencing the conventional learning model. This research uses a quantitative approach with a quasy experimental design type of research, pretest posttest control group design. The population in this study were all class VIII students at SMP Negeri 7 Langsa, and the sample consisted of classes VIII-1 and VIII-3 each with 21 students. Data collection was carried out using a descriptive question test instrument to measure students' mathematical reflective thinking abilities on two-variable linear equation systems. The research results show: (1) hypothesis testing using the paired sample t test, it can be concluded that there has been an increase in the reflective thinking abilities of students at SMP Negeri 7 Langsa after experiencing learning with the Connected Mathematics Project (CMP) model. (2) The increase in mathematical reflective thinking skills in the experimental class after experiencing learning with the Connected Mathematics Project (CMP) model was better than the control class after experiencing the conventional learning model. Researchers hope that the results of this research can be used as consideration and input for teachers in using the connected mathematics project (CMP) learning model to improve students' reflective thinking abilities.